2023
DOI: 10.1021/acsnano.3c04726
|View full text |Cite
|
Sign up to set email alerts
|

Echinacoside-Zinc Nanomaterial Inhibits Skin Glycation by Suppressing the Transcriptional Activation of the Receptor for Advanced Glycation End-Products

Abstract: Glycation is a nonenzymatically catalyzed spontaneous reaction that eventually leads to the formation of advanced glycation end-products (AGEs), which can bind to the receptor for AGEs (RAGE). The consequences are oxidative damage, an inflammatory response, and aging. In this work, we synthesized echinacoside-zinc coordination polymers (ECH-Zn) by using the coordination interaction between the catechol group of ECH and zinc ions. ECH-Zn was further wrapped with hyaluronic acid/poly (ethylenimine) (HA-PEI) to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Advanced glycation end-products (AGEs) have been shown to influence various biological processes. For instance, recent studies indicate that AGEs can regulate skin glycation by inhibiting specific transcription activators [ 38 ]. Additionally, the use of dual-channel fluorescence probes has enhanced the accuracy of detecting intracellular changes, which is crucial for understanding the relationship between AGEs and blood glucose levels [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Advanced glycation end-products (AGEs) have been shown to influence various biological processes. For instance, recent studies indicate that AGEs can regulate skin glycation by inhibiting specific transcription activators [ 38 ]. Additionally, the use of dual-channel fluorescence probes has enhanced the accuracy of detecting intracellular changes, which is crucial for understanding the relationship between AGEs and blood glucose levels [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…SPR technology was utilized to elucidate the mechanism through which PPZn nanoparticles (HA-PEI (hyaluronic acid/poly(ethylenimine))-coated ECH-Zn (echinacoside-zinc)) exert their antiglycation effect by regulating RAGE (Advanced glycosylation end product-specific receptor) via MDM2 (mouse double minute 2) and STAT2 (Signal transducer and activator of transcription 2). 83 SPR experiments revealed that ECH-Zn binds directly to STAT2 in a concentration-dependent manner, with no significant affinity observed between ECH-Zn and MDM2. To further validate the binding region of ECH-Zn with STAT2, truncated protein experiments involving STAT2 600−75 and STAT2 Δ600−750 were conducted.…”
Section: Spr In Nanoparticle Research For Biomedical Applicationmentioning
confidence: 91%
“…76 Synthesised echinacoside-zinc coordination polymers (ECH-Zn) fought against skin glycation through inhibiting the function of the MDM2/STAT2 complex and transcriptional activation of RAGEs. 77 3. Chemicals for breaking the AGEs cross-links.…”
Section: Chemicals Against Advanced Glycation End Productsmentioning
confidence: 99%
“…Fluorofenidone (AKF‐PD) reduces renal oxidative stress in mice by down‐regulating niacinamide adenine dinucleotide phosphate (NADPH) oxidase, glutathione peroxidase and glutathione superoxide dismutase through AGEs/RAGE/Nox pathway, thereby protecting mice from pathological damage caused by diabetic nephropathy 76 . Synthesised echinacoside‐zinc coordination polymers (ECH‐Zn) fought against skin glycation through inhibiting the function of the MDM2/STAT2 complex and transcriptional activation of RAGEs 77 Chemicals for breaking the AGEs cross‐links.…”
Section: Eliminations Of Advanced Glycation End Productsmentioning
confidence: 99%